2014
DOI: 10.1007/s10113-014-0648-2
|View full text |Cite
|
Sign up to set email alerts
|

The status of climate change adaptation in Africa and Asia

Abstract: Adaptation is a key component of climate policy, yet we have limited and fragmented understanding of if and how adaptation is currently taking place. In this paper, we document and characterize the current status of adaptation in 47 vulnerable 'hotspot' nations in Asia and Africa, based on a systematic review of the peer-reviewed and grey literature, as well as policy documents, to extract evidence of adaptation initiatives. In total, 100 peerreviewed articles, 161 grey literature documents, and 27 United Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
124
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 173 publications
(133 citation statements)
references
References 44 publications
8
124
1
Order By: Relevance
“…Even in regions with relatively high project involvement, such as East and South Africa, participation at the country level is fairly unequal. This finding is consistent with other studies in this special edition (e.g., Ford et al 2014) and other publications (Barr et al 2010), indicating that projects allocated by international agencies not only depend on a country's vulnerability, but also its implementation capacity to manage the funds. For example, countries such as Botswana, Chad, Gabon, Liberia, Uzbekistan, Turkmenistan and Zimbabwe share high vulnerability, a low adaptive capacity and a limited capacity to implement projects (Barr et al 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Even in regions with relatively high project involvement, such as East and South Africa, participation at the country level is fairly unequal. This finding is consistent with other studies in this special edition (e.g., Ford et al 2014) and other publications (Barr et al 2010), indicating that projects allocated by international agencies not only depend on a country's vulnerability, but also its implementation capacity to manage the funds. For example, countries such as Botswana, Chad, Gabon, Liberia, Uzbekistan, Turkmenistan and Zimbabwe share high vulnerability, a low adaptive capacity and a limited capacity to implement projects (Barr et al 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Ford et al (2014) find that trends in reported adaptation policy and practice differ substantively by literature source, highlighting the extent to which results are highly sensitive to the choice of document types included in a review. Quantitative and even formal qualitative evaluations of adaptation policy and practice efficacy are likely to be limited.…”
Section: Literature and Information Sourcesmentioning
confidence: 92%
“…In contrast, for a research question with a very large and diverse amount of information, the reviewer may need to identify ways of placing limits on the review so that it can be feasibly conducted. This might involve restricting the review to a single literature source (e.g., peer-reviewed articles, articles indexed only in Web of Knowledge), or selecting a sample of the literature (e.g., Ford et al 2014;Kilroy 2015;Kamau and Mwaura 2013). A reviewer must place limits on the amount of literature that can be covered, and this may be done at the defining/scoping stage (Pawson et al 2005).…”
Section: Literature and Information Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes careful adaptation planning imperative, as climate change is projected to increase temperatures, alter the temporal and spatial distribution of rainfall and increase the severity of droughts and flooding across the region (Niang et al 2014). Climate impacts are taking place alongside rapid social, economic and demographic transitions that combine to influence development outcomes, including interacting challenges across the nexus of food security (Ford et al 2015), water availability and energy supply (Conway et al 2015). Climate adaptation planning is subject to challenges of the paucity of reliable climate information (Jones et al 2015) and uncertainties about the timing of impacts and their spatial distribution (Davis 2011).…”
Section: Introductionmentioning
confidence: 99%